Endodontic Treatment of a Maxillary First Premolar with Type IV Buccal Root Canal: A Case Report - Dadresanfar, Bahareh; Khalilak, Zohreh; Shahmirzadi, Solaleh (Iranian Endodontic Journal, 2009)
The maxillary first premolar may present large number of anatomic variations. The clinician should be aware of the configuration of the pulp system. Maxillary first premolars usually have two canals. The incidence of three canals in these teeth is quite rare. This case report presents the diagnosis and clinical management of a maxillary first premolar with two distinct canals in the apical third of buccal root (type IV), drawing particular attention to tactile examination of all the canal walls.